2016
DOI: 10.4167/jbv.2016.46.3.152
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Hematological Characteristics, Including Cholesterol and Apolipoprotein B and E, between Hepatitis B Virus and Hepatitis C Virus Patients in Korea

Abstract: Hepatitis B virus (HBV) and hepatitis C virus (HCV) chronically cause hepatitis, liver cirrhosis, and hepatocellular carcinoma, and biomarkers related to liver damage are elevated in HBV and HCV patients. However, comparisons of biomarkers between HBV and HCV patients have not previously been reported. The aim of this study was to investigate differences in hematological biomarker in the sera of HBV and HCV patients and to find a key biomarker to differentiate between HBV and HCV infections. HBV (n=115) and HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(4 reference statements)
2
1
0
Order By: Relevance
“…Also very high increment in both ALT and/or GGT obtained in this study can provide a valuable information through the assessment of hepatic inflammation and fibrosis and beside Plt no other biochemical tests have been shown to be a better indicators of liver injury. Another important mediator of host immune defence CRP and Alb showed level increment in sera of HBV individuals compared with controls at (P≤0.05) , our finding is in agreement with other studies [16,30], these findings sound not unusual since liver is the target, organ for the replication of HBV , leading to the demolition of hepatocytes and, consequently increase the releasing of these molecules [18]. The effect of HBV infection on liver's clearance of pancreatic enzymes was followed by evaluation of Amy activity, Table 1, revealed significant increase(p≤0.05) in Amy activity in HBV patients compared with control group, our results are in agreement with Katakura Yet al [36], and Kaur N et al [19].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also very high increment in both ALT and/or GGT obtained in this study can provide a valuable information through the assessment of hepatic inflammation and fibrosis and beside Plt no other biochemical tests have been shown to be a better indicators of liver injury. Another important mediator of host immune defence CRP and Alb showed level increment in sera of HBV individuals compared with controls at (P≤0.05) , our finding is in agreement with other studies [16,30], these findings sound not unusual since liver is the target, organ for the replication of HBV , leading to the demolition of hepatocytes and, consequently increase the releasing of these molecules [18]. The effect of HBV infection on liver's clearance of pancreatic enzymes was followed by evaluation of Amy activity, Table 1, revealed significant increase(p≤0.05) in Amy activity in HBV patients compared with control group, our results are in agreement with Katakura Yet al [36], and Kaur N et al [19].…”
Section: Discussionsupporting
confidence: 93%
“…The marked increase of acutephase CRP occurs with inflammations, viral infections and tissue necrosis [16]. Nemours studies have performed on the relationship of CRP with the severity of inflammation in liver diseases, such HBV [13], [16][17][18]. An increase of pancreatic enzymes is generally an expression of inflammatory disease or pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…HCV infection is associated with a decrease in serum levels of total cholesterol, LDL cholesterol (18). In previous study, we already confirmed that HCV infection are strongly associated with low levels of main cholesterol biomarker (HDL, LDL, and total cholesterol) (12). We reconfirmed it through this study.…”
Section: Hcv Genotype Distribution and Gene Characteristicssupporting
confidence: 77%